The Role of Temporary Employees in Strengthening Subdistrict Organizations and Its Implications on Government Performance - Mukroni, Mukroni; Tjenreng, Muhammad Baharuddin Zubakhrum (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study aims to analyze the factors influencing the strengthening of sub-district organizations through the increase in honorary staff and its impact on government performance in South Tangerang City. Strengthening sub-district organizations is a key aspect of improving the effectiveness and efficiency of local government administration. Honorary staff, as supporting resources at the sub-district level, play a strategic role in enhancing organizational capacity. Methodology/approach: The research employs a qualitative approach with a case study design, focusing on South Tangerang City. Data were collected through in-depth interviews and observations involving participants from various sub-districts. Data were analyzed using thematic analysis to explore the perspectives on the relationship between the increase in honorary staff, the strengthening of sub-district organizations, and government performance. Results/findings: The findings indicate that an increase in honorary staff significantly contributes to strengthening sub-district organizations, which in turn positively impacts government performance at the sub-district level. Conclusion: The study concludes that increasing honorary staff strengthens sub-district organizations and improves government performance. However, sustainable outcomes require integrated policies ensuring status certainty, ongoing training, and a supportive work environment. Limitations: The study focuses only on sub-district organizations in South Tangerang City, and the results may not be generalizable to other regions with different governance structures. Contribution: This research provides important policy implications for optimizing human resources at the sub-district level to enhance public services and improve governance.